GRADUATE NURSES IDENTITY FROM DISTANCE LEARNING CURRICULUM - Siritarungsri, Boontip; Putapitakpol, Somjai (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Over the past decade of nursing shortage crisis in Thailand, only Sukhothai Thammathirat Open University (STOU), a public university, has provided a distance learning program to promote graduate nurses who wish to work and study concurrently. It, however, is still doubtful whether or not STOU graduate nurses identity suits the 21st century nursing criteria. The purpose of this mixed method research were: 1) to study identity of graduates from the Master of Nursing Science Program in Nursing Administration at STOU, and 2) to explore potential guidelines for the distance learning curriculum development in the Master of Nursing Science Program in the 21st century. The sample comprised of: (1) 268 graduate nurses from the program during academic year 2007-2014, 132 co-workers, and 130 supervisors, and (2) 15 representatives of the aforementioned groups, and (3) 13 academic experts. The research tool was a questionnaire relating to 7 identity characteristics of master graduates. Data analysis included descriptive statistics, T-Test, and contents analysis. The research results are as follows. 1) The graduate nurses' identity is being self-directed learning, applying knowledge into work development, using information and communication technology (ICT) in nursing administration to improve well-being of the people. 2) To add the course contents intended to improve communication competency, particularly English, in the areas of listening, reading, writing and speaking regarding innovation and technology for research in nursing administration. Up to this point, the identity characteristics appropriately serve to graduate characteristics in the 21st century. To strengthen international competency of nurses, it is therefore necessary to include more English courses in the distance learning curriculum.